Austenite reversion kinetics and stability during tempering of an additively manufactured maraging 300 steel - Conde, F. F. (2020)
FAPESP (2017/17697-5) FAPESP (2008/57863-0) FAPESP (2014/20844-1) FAPESP (2019/00691-0) CNPq (573661/2008-1) UID/EMS/00667/2019